Giant ethmoidal sinus osteoma with intraorbital extension: a case report (Bangladesh Journal of Medical Science, 2014)
Osteoma is the most frequent benign tumor of paranasal sinuses. Usually osteomas are asymptomatic and discovered incidentally during radiological imaging for other reasons. A giant osteoma with intraorbital extension is rare. Plain radiograph may be useful; however CT scan is the best modality of investigation for diagnosing and treatment planning. In asymptomatic osteomas, serial follow-up can be done. Surgery is performed in the presence of symptoms and signs. We report a case of 60 years old woman with a large osteoma of right ethmoid sinus extending into the ipsilateral orbital cavity. DOI: http://dx.doi.org/10.3329/bjms.v14i1.20925 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.95-97